MANAJEMEN MONITORING BERBASIS INDIKATOR KINERJA UTAMA DI LEMBAGA PENDIDIKAN ISLAM - Agus Karjuni; Tomi Apriyadi (Eduvis : Jurnal Manajemen Pendidikan Islam, 2023)
Background Monitoring management in Islamic educational institutions remains largely fragmented, lacking systematic Key Performance Indicators that align institutional goals with measurable outcomes. Objective: This study aims to examine conceptual frameworks for Key Performance Indicator (KPI)-based monitoring management and to formulate implementable models relevant to Islamic educational institutions. Methodology A library research methodology was employed, drawing on authoritative books and reputable scientific journals published within the last five years. Data were collected through documentation and content analysis techniques, followed by validity testing using source triangulation and referential adequacy. Results Findings reveal that KPI-based monitoring management significantly enhances institutional accountability, transparency, and continuous improvement when implemented through structured planning, measurement, evaluation, and feedback cycles. Integration of Islamic values into KPI frameworks produces a culturally congruent performance management system.